1992
DOI: 10.1111/j.1460-2695.1992.tb00062.x
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue Behaviour of Three Variants of the Roller Bearing Steel Sae 52100

Abstract: Stress-controlled, low-cycle, push-pull fatigue tests were performed on three variants of the bearing steel SAE 52100 with slightly different compositions and heat treatments. The experiments demonstrated differences in the cyclic plastic behaviour of differently hardened steels (bainitically-hardened and martensitically-hardened, respectively), whereas the two martensitic variants, which differ in composition, behaved very similarly. Bainitically-hardened SAE 52100 steel exhibited initial hardening followed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 18 publications
1
8
0
1
Order By: Relevance
“…Hence, both methods has been employed in this study; the actual strain range after a number of cycles would reach the value lower than 5.5×10 −4 predicted via the averaging method and near to 3.5×10 −4 obtained by the displacement method. Despite the different acquisition methods of previous studies [3][4][5], all data showed ∆γ C in the order of 10 −4 , supporting the results obtained in this study. Only the value used by Bhargava et al [6] and Hahn et al [12] for their calculations is significantly higher (Fig.…”
Section: Materials Response (∆γ C and Pmax )supporting
confidence: 89%
See 1 more Smart Citation
“…Hence, both methods has been employed in this study; the actual strain range after a number of cycles would reach the value lower than 5.5×10 −4 predicted via the averaging method and near to 3.5×10 −4 obtained by the displacement method. Despite the different acquisition methods of previous studies [3][4][5], all data showed ∆γ C in the order of 10 −4 , supporting the results obtained in this study. Only the value used by Bhargava et al [6] and Hahn et al [12] for their calculations is significantly higher (Fig.…”
Section: Materials Response (∆γ C and Pmax )supporting
confidence: 89%
“…In other words, conventional bearing testing methods cannot determine the experienced strain for the stress cycles due to the spatial and temporal variation in the stress state. As a result, structural fatigue tests have been carried out to obtain the strain range in cyclic torsion [3] and push-pull tests [4]. However, not enough data were obtained for stress-controlled tests, and the stress-strain responses used for calculations vary.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning the cyclic loading, martensitic or bainitic steels have typical fatigue behaviour: an overall significant softening till rupture [9][10][11][12][13][14][15][16][17][18][19][20] as shown in Fig. 2.…”
Section: Tensile and Fatigue Propertiesmentioning
confidence: 99%
“…However, the role of RA, which is of essential importance in high-carbon steels, has been a controversial subject in controlling both wear and fatigue behavior, 4) the reported data and results seem scattered and lack of systematic research. 3,12,13) The underlying mechanism of cryogenic treatment on RA is far from being well understood, more efforts and examinations should be devoted to assess the thermal stability of RA. It is noteworthy that the presence of metastable phases in the multiphase structures will in turn provide the new possibilities to optimization of industrial processing routes to achieve the extraordinary high-quality of the steels and products.…”
Section: Introductionmentioning
confidence: 99%